Internet of Things and Wireless Sensor Networks for Smart Agriculture Applications: A Survey - Mowla, Md. Najmul; Mowla, Neazmul; Shah, A. F. M. Shahen; Rabie, Khaled M.; Shongwe, Thokozani (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
The increasing food scarcity necessitates sustainable agriculture achieved through automation to meet the growing demand. Integrating the Internet of Things (IoT) and Wireless Sensor Networks (WSNs) is crucial in enhancing food production across various agricultural domains, encompassing irrigation, soil moisture monitoring, fertilizer optimization and control, early-stage pest and crop disease management, and energy conservation. Wireless application protocols such as ZigBee, WiFi, SigFox, and LoRaWAN are commonly employed to collect real-time data for monitoring purposes. Embracing advanced technology is imperative to ensure efficient annual production. Therefore, this study emphasizes a comprehensive, future-oriented approach, delving into IoT-WSNs, wireless network protocols, and their applications in agriculture since 2019. It thoroughly discusses the overview of IoT and WSNs, encompassing their architectures and summarization of network protocols. Furthermore, the study addresses recent issues and challenges related to IoT-WSNs and proposes mitigation strategies. It provides clear recommendations for the future, emphasizing the integration of advanced technology aiming to contribute to the future development of smart agriculture systems.
Keywords: Internet of Things; Artificial intelligence; Soil moisture; Smart agriculture; wireless sensor networks; wireless network protocols; smart agriculture applications; ARTIFICIAL-INTELLIGENCE; ROUTING PROTOCOL; DATA LINK; IOT; SYSTEM; IRRIGATION; DESIGN; ENERGY; FIELD; TECHNOLOGIES; Computer Science; Engineering; Telecommunications